Executive functioning of patients with congenital heart disease: 45 years after surgery. (3rd October 2022) - Pelosi, C; Kauling, R M; Cuypers, J A A E; Utens, E M W J; Van Den Bosch, A E; Kardys, I; Bogers, A J J C; Helbing, W A; Roos-Hesselink, J W; Legerstee, J S
Abstract: Background: For children with congenital heart disease (CHD), subtle neuropsychological deficits have been reported. However, very little is known about executive functioning in their adulthood. Purpose: To investigate the self- and informant-reported executive functioning in adults with CHD operated in childhood (<15 years old). Material and methods: A cohort study of 194 patients (age 50 [46–54] years), operated in childhood between 1968 and 1980 for one of the following diagnosis: atrial septal defect (ASD), ventricular septal defect (VSD), pulmonary stenosis (PS), tetralogy of Fallot (ToF) or transposition of the great arteries (TGA), were evaluated 40–53 years after surgery. The "Behavior Rating Inventory of Executive Functions – Adult version" (BRIEF-A) questionnaire was used to assess self- and informant-reported executive functioning and compared to the general population. Results: The CHD group did not show worse executive functioning compared to normative data. In addition, no significant difference was found between simple CHD (ASD, VSD and PS) and moderate/complex CHD (ToF and TGA). Higher education and NYHA class 1 were associated with better self-reported executive functioning, while male patients and patients taking psychiatric or cardiac medications reported worse executive functioning. Conclusions: Overall, our findings suggest reassuring outcomes regarding executive functioning in adults with CHD. However, these findings should be confirmed with neuropsychological assessment studies. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Thorax Foundation